Fibronectin stimulates the osteogenic differentiation of murine embryonic stem cells. (9th October 2015) - Kang, Yunyi; Georgiou, Anastasia I.; MacFarlane, Robert J.; Klontzas, Michail E.; Heliotis, Manolis; Tsiridis, Eleftherios; Mantalaris, Athanasios
Abstract: Conditioned medium from human hepatocarcinoma cells (HepG2‐CM) has been shown to stimulate the osteogenic/chondrogenic differentiation of murine embryonic stem cells (mESCs). HepG2‐CM is considered to contain visceral endoderm (VE)‐like signals and attempts have recently been made to characterize it, using proteomic profiling, with fibronectin being identified as one promising candidate. Herein, we investigated whether fibronectin is able to mimic the activities of HepG2‐CM during the osteogenic differentiation of mESCs. Specifically, the addition of RGD peptides and heparin in HepG2‐CM significantly reduced the growth‐ and adhesion‐promoting effects of HepG2‐CM, in addition to suppressing its osteogenic‐inductive activity. Furthermore, direct addition of fibronectin to basal medium was able to reproduce, at least partially, the function of HepG2‐CM. In particular, fibronectin induced the early onset of osteogenic differentiation in mESCs, as confirmed by gene expression of osteogenic markers, and resulted in the three‐fold higher calcium deposition at day 11 of osteogenic culture compared to the control group. These data clearly suggest that fibronectin contributes to the biological activities of HepG2‐CM and plays a stimulatory role during the process of osteogenesis in mESCs. Copyright © 2015 John Wiley & Sons, Ltd.